1976
DOI: 10.1002/pssa.2210380132
|View full text |Cite
|
Sign up to set email alerts
|

Thermal depolarization in crystals of potassium chloride containing strontium chloride

Abstract: Thermal depolarization has been measured for crystals of KCl doped with SrCG. Suoh crystals annealed at 623 K for one hour and then quenched display one major relaxation peak characterized by an activation energy of 0.74 eV. But if the annealing time is extended to 15 h a t the same temperature two relaxation processes with activation energies of 0.68 and 0.74 eV are observed. The dependence of the dipole relaxation spectrum on annmling time a t 250 K is measured. It is concluded that the relaxation process wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1977
1977
1993
1993

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In the case of KCl such an analysis has been carried out by Benière et al [1] for the anion doping they have used K2SO4 and they found that the migration enthalpy h',-and entropy s',-for the free anion vacancy is 0.85 eV and 3.2 k respectively. In the same experiment the analysis showed that the migration enthalpy hm,+ for the free cation motion is 0.73 eV ; this latter value is comparable to those corresponding to a bound cation vacancy motion [2] obtained by the dielectric loss [3] or ITC (Ionic Thermocurrents) [4] techniques (provided that the ionic radius of the divalent cation dopant is not much smaller than that of K+). Unfortunately, to the best of our knowledge, no value of the migration enthalpy hm'bfor the bound anion vacancy in KCI has been published up to date.…”
mentioning
confidence: 85%
“…In the case of KCl such an analysis has been carried out by Benière et al [1] for the anion doping they have used K2SO4 and they found that the migration enthalpy h',-and entropy s',-for the free anion vacancy is 0.85 eV and 3.2 k respectively. In the same experiment the analysis showed that the migration enthalpy hm,+ for the free cation motion is 0.73 eV ; this latter value is comparable to those corresponding to a bound cation vacancy motion [2] obtained by the dielectric loss [3] or ITC (Ionic Thermocurrents) [4] techniques (provided that the ionic radius of the divalent cation dopant is not much smaller than that of K+). Unfortunately, to the best of our knowledge, no value of the migration enthalpy hm'bfor the bound anion vacancy in KCI has been published up to date.…”
mentioning
confidence: 85%
“…Experimental J(T) curves can be computer fitted [8] to Equation 1 to yield numerical values of P0, E and t0. In the present work, thermally stimulated depolarization current measurements in the case of gel-grown KDP (KH2PO4) crystals doped with divalent anionic impurities like oxalate (C204): and carbonate (CO3) 2-have been reported.…”
mentioning
confidence: 99%